Digital Text through Hot Potatoes in Supporting Online Learning in Digital Society - Siregar, Syamsiah Depalina; Jasmienti, Jasmienti; Anggraini, Dian (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
Pandemic era stressed the lecturer to create innovative learning process. The article aimed to show up the benefit of hot potatoes in online learning. Hot potatoes is one of applications which consists of 6 tools in making interactive exercises. They are J Quiz, J Cross, J Cloze, J Mix, J Match, the masher. It helps lecturer managed exercises based digital text. It can used on offline. This article used research and development by Addie. There are five steps in Addie model. They are Analysis, design, develop, implementation, and evaluation. Data found that hot potatoes supported students in learning process. They more enjoy in completed the exercises on hot potatoes. Digital text used is decreasing the using of hardcopy, it help students saving the cost.